Palangka Raya People’s Responses to the Governor's Circular on Covid-19 Pandemic - Natalia, Desi (TEMALI : Jurnal Pembangunan Sosial, 2023)
Circular of the Governor of Central Kalimantan Number 443.2/20/BU, namely promoting social distancing by staying away from mass gatherings. Through these provisions, the government seeks to achieve a common goal: to prevent and minimize the spread of the covid-19 virus. This investigation that has been carried out seeks to understand the reality felt by residents of Palangka Raya. Researchers used qualitative research methods with a descriptive narrative approach. Data sources come from observations, interviews, and studies of references related to community responses, Governor's circular, and social actions. The results of the study explain that it has been proven that the essential thing in rejecting and reducing the spread of the Covid-19 virus is that there is a link between the level of education, knowledge, realization, and realistic actions, as well as the love that exists for these citizens in understanding and implementing government regulations, as well as regarding the benefits of implementing social distancing. This explains the sociological and theological phenomena through some of these linkages in the context of the Covid-19 pandemic, a form of instrumental action.